2005
DOI: 10.1177/1043454204273881
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Camp on Health-Related Quality of Life in Children With Chronic Illnesses: A Review of the Literature

Abstract: Chronic illness in children may negatively affect aspects of health-related quality of life (HRQL). Over many years, camps have been organized to address the physical and psychosocial needs of children with various chronic illnesses, while providing a "normal" as possible camp experience. The aim of this study was to critically review all research examining the effect of camps on HRQL in children with chronic illnesses. The literature review yielded no randomized, controlled clinical trials; 8 pretest-posttest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 45 publications
3
53
0
1
Order By: Relevance
“…Within a context of occupation these are potentially significant developmental gains. Interestingly, such findings are congruent with studies which explore the impact of summer camp attendance within non-war contexts [25]. Whether children would have made measurable gains on standardised measures in these factors is unknown, however, this finding, supported by summer camp workers perceptions, does affirm that summer camps through their milieu and psycho-social activities may have a role in growing children positive experiences and potentially increasing their resilience .…”
Section: Discussionsupporting
confidence: 74%
“…Within a context of occupation these are potentially significant developmental gains. Interestingly, such findings are congruent with studies which explore the impact of summer camp attendance within non-war contexts [25]. Whether children would have made measurable gains on standardised measures in these factors is unknown, however, this finding, supported by summer camp workers perceptions, does affirm that summer camps through their milieu and psycho-social activities may have a role in growing children positive experiences and potentially increasing their resilience .…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies on family caregivers of people with chronic health problems revealed higher level of burden, stress, and depression (Canam and Acorn 1999). Although it has been argued that all chronic illnesses and disabilities in children can negatively affect the health-related quality of life of the parents, each disease presents unique challenges (Epstein et al 2005). Moreover, an analysis of both qualitative and quantitative data indicate that primary carers are at considerable risk of high stress, clinical depression, and report substantially low subjective quality of life (SQoL) (Cummins 2001).…”
mentioning
confidence: 99%
“…Camps for children with chronic conditions have been reported and appear to be associated with some success in terms of therapeutic outcomes. 26 A set of first-hand accounts of the families' perspectives on JHD has been published, 27,28 but these accounts have not been subjected to thematic analysis. Nonetheless, some of the themes reported here can be discerned in those accounts together with aspects that gave hope and/or fulfillment despite the losses.…”
Section: Discussionmentioning
confidence: 99%